2024
DOI: 10.1590/1519-6984.258476
|View full text |Cite
|
Sign up to set email alerts
|

Salt stress and organic fertilization on the growth and biochemical metabolism of Hylocereus costaricensis (red pitaya) seedlings

Abstract: Red pitaya (Hylocereus costaricensis) is a promising species, with high cultivation potential due to the organoleptic and functional qualities of its fruits. However, irrigation water salinity can affect the crop yield. Therefore, materials rich in organic substances can minimize the damage caused by excess salts in soil and/or water. Thus, the objective of this study was to evaluate the influence of organic matter sources as attenuators of salt stress on the production and biochemical responses of red pitaya … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Unfortunately, the environments in which Ginkgo trees thrive are increasingly affected by salinity stress, which can impede their growth [3,4]. Excessive salinity adversely affects plant life, hindering seed germination [5][6][7][8] and overall growth and development [9,10], and disrupting photosynthesis [11]. This results in issues such as compromised dry matter accumulation [12], osmotic stress [13], ionic toxicity [14], and oxidative stress [15,16], potentially leading to metabolic disruptions or plant mortality [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the environments in which Ginkgo trees thrive are increasingly affected by salinity stress, which can impede their growth [3,4]. Excessive salinity adversely affects plant life, hindering seed germination [5][6][7][8] and overall growth and development [9,10], and disrupting photosynthesis [11]. This results in issues such as compromised dry matter accumulation [12], osmotic stress [13], ionic toxicity [14], and oxidative stress [15,16], potentially leading to metabolic disruptions or plant mortality [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Organic matter has several positive effects, such as water retention, soil structure improvement, salts leaching, osmotic potential reduction in the soil solution, and release of Ca 2+ and Mg 2+ ions, which replace Na + in the exchange complex (Yousaf et al, 2021). Many studies in the literature report the effectiveness of organic matter in reducing the damage caused by salts in plants (Yarami & Sepaskhah, 2015;Naveed et al, 2020;Oliveira et al, 2022). Our findings corroborate those of Sousa et al (2018) and Sousa, Lacerda, Aguiar, and Praxedes (2017), who found increased growth of sorghum plants under saline stress associated with improvements in soil chemistry and increased soil fertility, promoted by the addition of organic matter.…”
Section: Discussionmentioning
confidence: 99%
“…While the literature has reported the isolated effects of these salt stress mitigators, further research is needed to assess the efficacy of their interactions (Yin et al, 2016;Gupta et al, 2021b;Oliveira et al, 2022). We hypothesize that combining organic matter and/or T. harzianum with silicon may enhance its mitigating effect, improving forage sorghum performance in saline environments in semiarid regions.…”
Section: Introductionmentioning
confidence: 99%